Effect of ultrasonic nanocrystal surface modification on microstructure and properties of 304 stainless steel - GAO Le; ZHANG Yu; YE Yixuan; PENG Lan; YE Chang (Cailiao gongcheng, 2024)
The surface strengthening treatment of 304 stainless steel was carried out by using ultrasonic nanocrystal surface modification （UNSM） technology， and the effect of UNSM on the microstructure and mechanical performance of stainless steel was studied. The microstructure evolution and plastic deformation mechanism before and after UNSM treatment were analyzed by transmission electron microscopy （TEM）， electron backscattered diffraction （EBSD） and other characterization methods. The effects of UNSM on surface roughness， microhardness and residual stress of materials were studied by using white light interferometry and microhardness testing. The results show that after UNSM treatment， 304 stainless steel undergoes severe plastic deformation on the surface， resulting in an increase in dislocation density and significant grain refinement， and nanocrystals are generated on the near-surface region， forming a hardened layer about 300 μm deep. The deformation induces austenite-to-martensite transformation and introduces the residual compressive stress of about 900 MPa on the surface. The microhardness of the material increases from 238HV to 511HV， and the surface integrity is significantly improved.